Surgical management of traumatic cardiac fistulae. Issue 5 (September 1969) - Rogers, Michael A.; Chesler, Elliot; Du Plessis, Louis
Abstract : Seven cases of traumatic intracardiac lesions following penetrating stab wounds of the heart are presented. The surgical management and complications encountered in these cases are discussed.